Assessing Waste Management Practices and Their Impact on Environmental Sustainability in Afghanistan - Zakhilwal, Shawkat Ali; Behsoodi, Mohammad Mukhlis; Aslam, Muhammad Sagheer (Indonesian Journal of Environmental Management and Sustainability, 2024)
This paper examines waste management’s impact on environmental sustainability in Afghanistan against the backdrop of global waste management challenges. Globally, unsustainable waste management practices contribute significantly to environmental degradation, with 1.3 billion tons of food wasted annually-one-third of global production exacerbating hunger for one in seven people. Global waste production has reached 2.01 billion tons annually, with construction contributing 35%. Packaging and paper waste account for 40-65% of waste treatment costs in Europe, and tourism adds 35 million tons of solid waste annually. Plastic waste production has risen to 300 million tons per year, threatening marine life with projections of sea pollution surpassing fish populations by 2050. In Afghanistan, financial and technical constraints lead to significant food loss and improper waste disposal, creating unsanitary environments and health hazards. Household waste mismanagement ranges from 20% to 80%, with Kabul generating 3,300 tons of waste per day by 2025, 70% of which is organic. Data from 127 respondents reveal a positive correlation (0.265) between waste management and sustainability, accounting for 26.5% of the variation, with a 0.249 coefficient confirmed at the 1% significance level.